장간막에 발생한 Castleman 질환 - 최병조(Byung Jo Choi); 김기환(Ki Whan Kim); 안창혁(Chang Hyeok An); 김정수(Jung Soo Kim); 유승진(Seung Jin Yoo); 임근우(Keun Woo Lim) (Annals of surgical treatment and research, 2005)
Castleman’s disease is a rare disorder characterized by tumorous masses that may develop in the lymph node tissue throughout the body. Most common location is mediastinum, but it can also affect retroperitoneum, neck, pelvis, and/or axilla. It may exceptionally affect extranodal sites like striated muscle, thoracic wall, lungs, skull, larynx, and/or vulva. The presentation is varied and diagnosis is difficult. There are two main types of Castleman’s disease: hyaline-vascular type and plasma cell type. The hyaline vascular type accounts for approximately 90% of the cases. Most individuals exhibit no symptoms of this form of the disorder or they may develop non-cancerous growths in the lymph nodes. The plasma cell type is often associated with fever, weight loss, skin rash, early destruction of red blood cells, leading to unusually low levels of circulating red blood cells (hemolytic anemia), and/ or abnormally increased amounts of certain immune factors in the blood (hypergammaglobulinemia). We here report a case of Castleman’s disease of ileal mesentery in 30-years old female patient. Abdominal mass, 4.7×3.6 cm in size, was completely removed from ileal mesentery without complication, and confirmed histologically mesenteric Castleman’s disease of the mixed type. KCI Citation Count: 1